2021
DOI: 10.3389/fonc.2021.709525
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic Profiling and Drug Screening of Patient-Derived Cultures Identifies Individualized Copy Number-Dependent Susceptibilities Involving PI3K Pathway and 17q Genes in Neuroblastoma

Abstract: Neuroblastoma is the commonest extracranial pediatric malignancy. With few recurrent single nucleotide variations (SNVs), mutation-based precision oncology approaches have limited utility, but its frequent and heterogenous copy number variations (CNVs) could represent genomic dependencies that may be exploited for personalized therapy. Patient-derived cell culture (PDC) models can facilitate rapid testing of multiple agents to determine such individualized drug-responses. Thus, to study the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…The study by Schleiermacher et al reported that 17q gain, along with 1p deletion and MYCN amplification, resulted in an exchange of genetic material that was replicated early in the cell cycle's S-phase [35]. Wong et al demonstrated dose-dependent relationships between the copy number gains of PI3K and STAT family genes on 17q and the susceptibility of NB to cell cycle and PI3K inhibitors [110]. 17q gain's importance in NB development was also demonstrated using animal models.…”
Section: Functional Gene Studiesmentioning
confidence: 99%
“…The study by Schleiermacher et al reported that 17q gain, along with 1p deletion and MYCN amplification, resulted in an exchange of genetic material that was replicated early in the cell cycle's S-phase [35]. Wong et al demonstrated dose-dependent relationships between the copy number gains of PI3K and STAT family genes on 17q and the susceptibility of NB to cell cycle and PI3K inhibitors [110]. 17q gain's importance in NB development was also demonstrated using animal models.…”
Section: Functional Gene Studiesmentioning
confidence: 99%
“…They also showed that the combination of seven markers can differentiate patients with localised and advanced stages of prostate cancer. Another important aspect of screening CNAs in cancer patient samples is the potential to identify if CNAs infer sensitivity or cytotoxicity to therapeutic agents, as recently shown in melanoma and neuroblastoma [96,97]. Wong et al correlated the gain of PPM1D/GNA13 genes or loss of CBL/DNMT3A genes with enhanced cytotoxicity, whilst gains of PI3K or STAT family genes sensitise neuroblastoma cells to cell cycle inhibitors [97].…”
Section: Somatic Cnas In Cancermentioning
confidence: 99%
“…Another important aspect of screening CNAs in cancer patient samples is the potential to identify if CNAs infer sensitivity or cytotoxicity to therapeutic agents, as recently shown in melanoma and neuroblastoma [96,97]. Wong et al correlated the gain of PPM1D/GNA13 genes or loss of CBL/DNMT3A genes with enhanced cytotoxicity, whilst gains of PI3K or STAT family genes sensitise neuroblastoma cells to cell cycle inhibitors [97]. Moreover, using the cancer proteome atlas, a predictive link between CNAs and phosphorylation changes has been discovered, providing a new potential readout to assess sensitivity to kinase inhibition in cancer [98].…”
Section: Somatic Cnas In Cancermentioning
confidence: 99%